The discovery of a five-image lensed quasar at z = 3.34 using PanSTARRS1 and Gaia. (24th October 2017) - Ostrovski, Fernanda; Lemon, Cameron A; Auger, Matthew W; McMahon, Richard G; Fassnacht, Christopher D; Chen, Geoff C-F; Connolly, Andrew J; Koposov, Sergey E; Pons, Estelle; Reed, Sophie L; Rusu, Cristian E
Abstract: We report the discovery, spectroscopic confirmation and mass modelling of the gravitationally lensed quasar system PS J0630−1201. The lens was discovered by matching a photometric quasar catalogue compiled from Pan-STARRS1 and Wide-field Infrared Survey Explorer photometry to the Gaia data release 1 catalogue, exploiting the high spatial resolution of the latter (full width at half-maximum ∼0.1 arcsec) to identify the three brightest components of the lensed quasar system. Follow-up spectroscopic observations with the William Herschel Telescope confirm the multiple objects are quasars at redshift z q  = 3.34. Further follow-up with Keck adaptive optics high-resolution imaging reveals that the system is composed of two lensing galaxies and the quasar is lensed into an ∼2.8 arcsec separation four-image cusp configuration with a fifth image clearly visible, and a 1.0 arcsec arc due to the lensed quasar host galaxy. The system is well modelled with two singular isothermal ellipsoids, reproducing the position of the fifth image. We discuss future prospects for measuring time delays between the images and constraining any offset between mass and light using the faintly detected Einstein arcs associated with the quasar host galaxy.